New developments in mechanotransduction: Cross talk of the Wnt, TGF-β and Notch signalling pathways in reaction to shear stress. (March 2018) - Abuammah, Aliah; Maimari, Nataly; Towhidi, Leila; Frueh, Jenny; Chooi, Kok Yean; Warboys, Christina; Krams, Rob
Abstract: Mechanotransduction, the ability of cells to detect and react to mechanical forces, is increasingly playing a critical role in a variety of physiological and pathophysiological processes. While the focus has previously been on the MAPK, NF-ϰB and ROS generating pathways, ancient embryological pathways have reached little attention. Recently, a surge of new studies have been published on these pathways and their role in mechanotransduction and this review paper aims to provide a concise overview on the latest studies and brings them in to a larger perspective. Special emphasis is on the non-canonical aspects of the Wnt, TGF-β and Notch pathways and their role in flow. Highlights: Previously pathways of the domain of embryology (Notch, Wnt, TGF-β) have been shown to be shear sensitive. In particular, their non-canonical variants seem to be important for blood flow related diseases like atherosclerosis. These three pathways seem to be interconnected forming a functional overarching network, which is sensitive to shear stress.